Input–output organization of the mouse BLA-projecting IL neurons - Li, Zhuo; Qu, Yu; Wu, Qi-Lin; Tang, Li; Dong, Yuan; Xu, Xu-Feng (Frontiers in Neuroscience, 2025)
IntroductionThe infralimbic cortex (IL), a critical subregion within the ventromedial prefrontal cortex (vmPFC), modulates emotion, memory, and social functions via robust projections to the basolateral amygdala (BLA). However, the afferent brain regions that innervate BLA-projecting IL neurons (IL-BLA PNs) and their efferent targets have not been systematically characterized.MethodsWe employed tracing techniques integrating adeno-associated virus (AAV) and monosynaptic rabies to systematically investigate the presynaptic inputs and axonal outputs of IL-BLA PNs.ResultsOur findings revealed widespread synaptic inputs to IL-BLA PNs from subcortical areas, with the strongest inputs originating from the dorsomedial thalamus (MD) and anterior medial thalamus (AM) in the thalamic region, as well as from the ventral hippocampus (vHPC) and piriform cortex (Pir) in the limbic system. Sparse labeling of the virus demonstrated that IL-BLA PNs collateralize to innervate various subcortical regions, including the horizontal diagonal band (HDB), lateral preoptic area (LPO), ventral pallidum (VP), and lateral hypothalamus (LH).DiscussionThis work establishes essential theoretical frameworks for the functional investigation and targeted intervention in neurological disorders.